Persistir en el intento: cambios y permanencias en la identidad y rol de las ONG fundacionales en el Perú 1990-2016 - Bobadilla Díaz, Percy (Pontificia Universidad Católica del Perú. Fondo Editorial, 2016)
This research aims to show the organizational changes and forms of social intervention that have been assumed by NGOs that were founded in Peru between the 60s and 80s. Since 1990 these NGOs have undergone a series of changes, mainly these have been given in the development discourses that guide their projects, in the type of relations that they establish with key actors to execute them and in the way to finance their operation. It will be noted that in the field of international and local development the rules of the game for NGOs are modified: the central State and the business sector acquire a greater presence in the promotion of development projects; There is a greater orientation to the market and selling services based on efficient management; And there is a context of reduction of funds coming from international cooperation agencies. This will generate the emergence of strategic roles as a way to respond to these changes in the institutional environment. It will be noted that, although strategies have been modified and new approaches are used - linked to human development, gender, environment, governance, among others - the meaning of NGOs’ foundational social action remain in force: working with vulnerable and excluded populations.

Esta investigación pretende mostrar los cambios organizacionales y las formas de intervención social que han venido asumiendo las ONG fundadas en el Perú entre las décadas de 1960 y 1980. A partir de 1990, estas ONG han sufrido una serie de cambios, principalmente en los discursos de desarrollo que orientan sus proyectos, en el tipo de relaciones que establecen con actores claves para ejecutarlos y en la manera de financiar su funcionamiento. Se observará que en el ámbito del desarrollo internacional y local se modifican las reglas del juego para las ONG: el Estado central y el sector empresarial incrementan su presencia en la promoción de proyectos de desarrollo; hay una mayor orientación al mercado y a la venta de servicios basados en una gestión eficiente; en un contexto de reducción de fondos provenientes de agencias de cooperación internacional. Esto generará el surgimiento de roles estratégicos como una manera de responder a estos cambios en el entorno institucional. Se notará que, si bien las estrategias se han modificado y utilizan nuevos enfoques —ligados al desarrollo humano, el género, medio ambiente, gobernabilidad, entre otros—, el sentido y significado de la acción social fundacional de las ONG se mantienen vigentes: el trabajo con poblaciones vulnerables y excluidas.
Persisting in the attempt: changes and permanence in the identity and role of foundational NGOs in Peru 1990 - -2016
Keywords: ONG; Identidad institucional; Identidad organizacional; Roles estratégicos; Cambio organizacional; https://purl.org/pe-repo/ocde/ford#5.04.00